Seal member, manufacturing method thereof and battery

A laminated sealing member with foam and non-foam silicone rubber layers addresses the issue of planar deformation in battery containers, maintaining thickness flexibility and enhancing sealing performance and manufacturing efficiency.

JP2025012522APending Publication Date: 2025-01-24SHIN ETSU POLYMER CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023115408
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Conventional sealing members for vehicle-mounted battery containers lose their shape due to high flexibility in the planar direction, leading to deformation and increased processing and installation costs.

Method used

A laminated sealing member composed of at least one foam layer and one non-foam layer, fixed in the thickness direction, which maintains flexibility in the thickness direction while suppressing flexibility in the planar direction, using curable silicone rubber layers that integrate without adhesives.

Benefits of technology

The laminated structure prevents deformation in the planar direction while maintaining flexibility in the thickness direction, ensuring effective sealing and ease of manufacturing, with improved deflection resistance and sealing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012522000001_ABST
    Figure 2025012522000001_ABST
Patent Text Reader

Abstract

To provide a seal member for a battery container that reduces flexibility in a planar direction, which may cause losing shape, while maintaining flexibility in a thickness direction, a manufacturing method thereof, and a battery comprising the seal member.SOLUTION: The present invention relates to an annular seal member 1 for sealing an opening / closing portion of an opening / closing type container for storing a plurality of battery cells 20, where the seal member 1 comprises at least one foam layer 2 and one non-foam layer 3, the foam layer 2 and the non-foam layer 3 being fixed in a laminated state in a thickness direction of the seal member 1, a manufacturing method thereof, and a battery 10 comprising the seal member 1.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealing member, a manufacturing method thereof, and a battery including the sealing member. [Background technology]

[0002] Automobiles have changed from the era when engines were the only power source to hybrid cars equipped with both engines and batteries, and further to electric cars equipped with only batteries. The on-board batteries of electric vehicles are large and susceptible to heat, so the fitting tolerance of the container becomes large. For this reason, foaming materials that can follow the tolerance are used as sealing materials for on-board battery containers. However, conventional sealing materials for on-board battery containers have the disadvantage that they easily lose their shape because they are large and highly flexible. To solve this problem, a method of providing positioning holes, grooves, and guides in the sealing material itself has been widely used (Patent Document 1), but there were problems such as high costs for processing the sealing material and the installation housing. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-122536 A Summary of the Invention [Problem to be solved by the invention]

[0004] FIG. 8 shows a schematic front view of a sealing member (A) conventionally used for battery containers, and the sealing member when force is applied from the thickness direction (B) and the planar direction (C). The white arrows in FIG. 8 indicate the direction in which force is applied. The sealing member 100 is mainly made of a foaming material (A) and has excellent flexibility in the thickness direction (the vertical direction in B) (B), and therefore can accommodate changes in the fitting tolerance of the container. However, the sealing member 100 is large in size and has high flexibility in the planar direction (the horizontal direction in C) (C), so it stretches when pulled, easily causing deformation.

[0005] The inventors aim to provide a sealing member for a battery container that maintains flexibility in the thickness direction while reducing flexibility in the planar direction that causes the container to lose its shape, a method for manufacturing the sealing member, and a battery equipped with the sealing member. [Means for solving the problem]

[0006] (1) In order to achieve the above object, a sealing member according to one embodiment is an annular sealing member for sealing an opening and closing portion of an open-close type container for storing a plurality of battery cells, The sheet has at least one foamed layer and at least one non-foamed layer, The foamed layer and the non-foamed layer are fixed in a laminated state in the thickness direction of the sealing member. (2) In the sealing member according to another embodiment, preferably, both the foamed layer and the non-foamed layer may be silicone rubber layers. (3) In the sealing member according to another embodiment, preferably, the non-foamed layer may be laminated on both sides of the foamed layer. (4) In the sealing member according to another embodiment, preferably, the foamed layer may be laminated on both sides of the non-foamed layer. (5) In order to achieve the above object, a method for producing a seal member according to one embodiment is the method for producing a seal member according to any one of the above-described aspects, A blending step of blending the raw materials of the foamed layer and the non-foamed layer; a sheeting step of forming the foamed layer and the non-foamed layer into a sheet shape after the blending step; a lamination step of laminating the foamed layer sheet formed in the sheeting step and the non-foamed layer sheet; a vulcanization step of vulcanizing and hardening the sheets bonded in the bonding step; Includes. (6) To achieve the above object, a battery according to one embodiment includes the sealing member described above. Effect of the Invention

[0007] According to the present invention, it is possible to provide a sealing member for a battery container that maintains flexibility in the thickness direction while suppressing flexibility in the planar direction that causes deformation, a manufacturing method thereof, and a battery including the sealing member. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 shows a plan view, a front view, and a rear view of a sealing member according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic front view of a sealing member to which a force is applied in the thickness direction (A) and the planar direction (B). [Diagram 3] FIG. 3 shows modified examples (A to C) of the seal member. [Figure 4] FIG. 4 shows an assembly diagram of a battery according to one embodiment of the present invention. [Diagram 5] FIG. 5 shows a schematic cross-sectional view of the battery of FIG. 4 after assembly. [Figure 6] FIG. 6 shows a process flow of a method for producing a seal member according to one embodiment of the present invention. [Figure 7] FIG. 7 shows the morphology and evaluation results of each sample of the examples and comparative examples. [Figure 8] FIG. 8 shows a schematic front view of a sealing member (A) that has been conventionally used in battery containers, and the sealing member to which force is applied in the thickness direction (B) and the planar direction (C). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Next, an embodiment of the present invention will be described with reference to the drawings. Note that the embodiment described below does not limit the invention according to the claims, and all of the elements and combinations thereof described in the embodiment are not necessarily essential to the solution of the present invention.

[0010] 1. Sealing materials and batteries Fig. 1 shows a plan view, a front view, and a back view of a sealing member according to one embodiment of the present invention, and Fig. 2 shows a schematic front view of the sealing member to which a force is applied from the thickness direction (A) and the planar direction (B).

[0011] The sealing member 1 according to this embodiment is an annular sealing member for sealing an opening and closing portion of an open-close type container for storing a plurality of battery cells. This sealing member 1 includes at least one foam layer 2 and one non-foam layer 3. The foam layer 2 and the non-foam layer 3 are fixed in a laminated state in the thickness direction of the sealing member 1.

[0012] In the present application, the "thickness direction" refers to the direction in which the foamed layer 2 and the non-foamed layer 3 of the sealing member 1 are laminated. The "planar direction" refers to the direction perpendicular to the thickness direction in the front view of the sealing member 1. In addition, the "non-foamed layer" does not mean a layer that does not have any pores, but may be a layer that contains a small number of pores as long as it is a layer formed without actively carrying out a foaming treatment.

[0013] From the viewpoints of achieving high flame retardancy and heat resistance and ability to conform to the dimensional accuracy of the gap at the opening and closing part of the battery container, both the foamed layer 2 and the non-foamed layer 3 constituting the sealing member 1 are preferably silicone rubber layers. In addition, since both layers of the sealing member 1 are manufactured using a curable silicone rubber composition, they can be integrated through a vulcanization process without the use of an adhesive or the like. This makes it extremely easy to manufacture the sealing member 1.

[0014] The white arrows in Fig. 2 indicate the direction in which force is applied. As shown in A, when the sealing member 1 is compressed in the thickness direction (the vertical direction in A), it is deformed so as to be crushed. On the other hand, as shown in B, even when the sealing member 1 is pulled in the planar direction (the horizontal direction in B), the foam layer 2 does not stretch due to the presence of the non-foam layer 3. Therefore, the sealing member 1 can conform to the tolerance of the battery container and does not lose its shape when installed.

[0015] The foam layer 2 is a suitable layer for sealing the gap of the battery container by following the fitting tolerance of the battery container. That is, even if the gap between the top lid, which is the opening and closing part of the battery container, and the container body varies depending on the location, the airtightness of the battery container can be maintained due to the high shrinkability in the thickness direction of the foam layer 2. The foam layer 2 is also called a sponge layer.

[0016] The shape of the foam layer 2 is annular because it is necessary to be able to seal between the openable and closable members of the battery container. The thickness and size of the foam layer 2 are not particularly limited as long as they are able to seal between the above-mentioned members, and can be changed in various ways depending on the dimensions of the battery container.

[0017] In this embodiment, the foam layer 2 is colored with a black pigment, but the color of the layer 2 is not limited thereto, and the layer 2 may be uncolored or colored with another color.

[0018] The non-foamed layer 3 is a layer for preventing the foamed layer 2 from losing its shape. The non-foamed layer 3 is bonded to the foamed layer 2 to form the sealing member 1, which is a laminate. A method for bonding the non-foamed layer 3 to the foamed layer 2 will be described later.

[0019] The non-foamed layer 3 has a ring-shaped shape like the foamed layer 2. The size of the non-foamed layer 3 is not particularly limited as long as it can seal between the above-mentioned members of the battery container.

[0020] The thickness of the non-foamed layer 3 is not particularly limited, but from the viewpoint of not impairing the conformability of the sealing member 1, it is preferably 1 / 20 to 1 / 10 times, and more preferably 1 / 18 to 1 / 12 times, the thickness of the foamed layer 2 after the vulcanization process.

[0021] In this embodiment, the non-foamed layer 3 is not colored, but the color of the layer 3 is not limited thereto, and the layer 3 may be colored in various colors.

[0022] The rubber hardness of the non-foamed layer 3 is not particularly limited, but is preferably higher than that of the foamed layer 2. Here, the rubber hardness refers to the hardness measured using a type A durometer based on JIS K 6253. The rubber hardness of the non-foamed layer 3 is preferably 35 to 90, more preferably 40 to 90, and particularly preferably 45 to 85. When the rubber hardness of the non-foamed layer 3 is equal to or lower than the upper limit, the flexibility of the non-foamed layer 3 itself in the compression direction is not impaired. When the rubber hardness of the non-foamed layer 3 is equal to or higher than the lower limit, the strength in the planar direction increases, and deformation of the seal member 1 can be prevented.

[0023] FIG. 3 shows modified examples (A to C) of the seal member.

[0024] The lamination state of the sealing member 1 is not particularly limited as long as at least one foamed layer 2 and at least one non-foamed layer 3 are fixed in the thickness direction. In the sealing member 1, the foamed layer 2 is disposed on the lower side and the non-foamed layer 3 is disposed on the upper side. However, as shown in A, the non-foamed layer 3 may be disposed on the lower side and the foamed layer 2 on the upper side.

[0025] The seal member 1 may have two or more foamed layers 2 and / or non-foamed layers 3. In this case, as shown in B, it is preferable that the non-foamed layers 3 are laminated on both sides of the foamed layer 2. It is also preferable that the foamed layers 2 are laminated on both sides of the non-foamed layers 3, as shown in C.

[0026] Fig. 4 shows an assembled view of a battery according to one embodiment of the present invention, and Fig. 5 shows a schematic cross-sectional view of the battery of Fig. 4 after assembly.

[0027] The battery 10 according to this embodiment is, for example, a battery for an electric vehicle, and includes a plurality of battery cells 20 arranged in a row. The number of battery cells 20 is six in this embodiment, but may be one to five or seven or more. The battery 10 is a type of storage battery, and is preferably a lithium ion battery. The battery 10 includes a bottomed container 11 that is open on one side. The battery cells 20 are disposed inside the container 11.

[0028] A battery 10 according to one embodiment is a battery including any one of the sealing members 1 described above. The battery 10 is assembled by covering a container 11 including a plurality of battery cells 20 with a top lid 12. During assembly, the sealing member 1 is placed on the outer edge of the container 11 and sandwiched between the top lid 12 and the container 11. The container 11 and the top lid 12 of the battery 10 may have screw holes 13 and 14 for attaching screws 15 and nuts 16 for assembly. In this case, it is preferable that the screw holes 13 and 14 are located outside the sandwiched sealing member 1. The container 11 and the top lid 12 may be fixed to each other by means other than the screws 15 and nuts 16.

[0029] 2. Manufacturing method of sealing member FIG. 6 shows a process flow of a method for producing a seal member according to one embodiment of the present invention.

[0030] A method for manufacturing a sealing member according to one embodiment is a method for manufacturing any one of the above-mentioned sealing members 1, and includes a blending step (S100) of blending the raw materials for the foamed layer 2 and the non-foamed layer 3, a sheeting step (S200) of forming the foamed layer 2 and the non-foamed layer 3 into a sheet shape after the blending step, a lamination step (S300) of laminating the sheet of foamed layer 2 and the sheet of non-foamed layer 3 formed in the sheeting step, and a vulcanization step (S400, S500) of vulcanizing and hardening the sheets laminated in the lamination step.

[0031] (1)Blending process (S100) This step is a step of blending the respective raw materials of the foamed layer 2 and the non-foamed layer 3. For example, when the foamed layer 2 and the non-foamed layer 3 are silicone rubber, this is a step of preparing a curable silicone rubber composition that is a raw material for the silicone rubber. This step preferably includes a step of mixing and kneading various materials. The curable silicone rubber composition includes known raw materials such as a silicone rubber base agent represented by organopolysiloxane, a crosslinking agent (also called a vulcanizing agent), a catalyst, and a filler. When the foamed layer 2 is a sponge-like silicone rubber, the curable silicone rubber composition preferably includes a foaming agent. Examples of the foaming agent include organic foaming agents represented by azobisisobutyronitrile (AIBN) or azodicarbonamide (ADCA). As an example of a method that does not include an organic foaming agent, a method of preparing a curable silicone rubber composition to which thermally expandable resin beads are added can be mentioned. In this case, the resin beads become balloon-like during curing, and a sponge-like cured body can be obtained. Another example of a method that does not use an organic foaming agent is to mix air under high pressure into a non-foaming liquid silicone rubber composition. In this case, a sponge-like cured product can be obtained by curing the curable silicone rubber composition under normal pressure.

[0032] (2) Sheeting process (S200) This step is a step of forming the foamed layer 2 and the non-foamed layer 3 into sheets using the raw materials after the blending step. The method of forming the sheets in this step is not particularly limited. For example, the mixed contents are placed in a mold and pressure-molded.

[0033] (3) Bonding process (S300) This step is a step of laminating the sheet of the foamed layer 2 formed in the sheeting step and the sheet of the non-foamed layer 3 into an integrated sheet. When at least one of the sheets of the foamed layer 2 and / or the non-foamed layer 3 is present in a plurality of sheets, the laminating step may be carried out successively or all at once.

[0034] (4) Primary vulcanization process (S400) This step is a part of the vulcanization step, and is a step of heating and curing the laminated sheets. In this step, bubbles are generated in the laminated sheets. The preferred temperature is 170 to 200°C.

[0035] (5) Secondary vulcanization process (S500) This step is a part of the vulcanization step, and is a step in which the sheet is further heated after the primary vulcanization to complete curing. In this step, the final thickness of the sheet is determined. The preferred temperature is 190 to 210°C. The vulcanization step may be a one-step step or a three or more-step step instead of the two-step step described above. EXAMPLES

[0036] Next, examples of the present invention will be described. Note that the present invention is not limited to the following examples.

[0037] 1. Manufacturing conditions Example 1 100 parts by mass of silicone compound (product number: KE-541-U, for rubber hardness 40) manufactured by Shin-Etsu Chemical Co., Ltd., 0.3 parts by mass of vulcanizing agent (product number: C-1A) manufactured by Shin-Etsu Chemical Co., Ltd., 2.3 parts by mass of vulcanizing agent (product number: C-3) manufactured by Shin-Etsu Chemical Co., Ltd., 1.0 parts by mass of organic foaming agent "azobis-isobutyronitrile", and 1.0 parts by mass of black pigment (product number: KE-COLOR-CB) manufactured by Shin-Etsu Chemical Co., Ltd. were mixed and kneaded to prepare a compound for sheet molding. Next, the compound after kneading was rolled through two rolls adjusted to a gap of 1.3 mm and molded into a sheet. Such molding was performed once to prepare one sheet for the foam layer. This is referred to as a "sheet for the foam layer". Here, 1 part by mass = 10 g. The same applies to the examples and comparative examples described later.

[0038] Next, 100 parts by mass of a silicone compound (product number: KE-541-U, for rubber hardness 40) manufactured by Shin-Etsu Chemical Co., Ltd. and 2.3 parts by mass of a vulcanizing agent (product number: C-3) manufactured by Shin-Etsu Chemical Co., Ltd. were mixed and kneaded to prepare a compound for sheet molding. Next, the compound after kneading was rolled through two rolls with a gap adjusted to 0.3 mm to be molded into a sheet. This molding was performed once to prepare one sheet for the non-foamed layer. This is referred to as the "sheet for the non-foamed layer."

[0039] Next, the foam layer sheet and the non-foam layer sheet were laminated together and pressed through two rolls to bond them together.

[0040] Next, the laminated sheets were hung in a room at 190°C for 5 minutes to carry out primary vulcanization. During this vulcanization, the foam layer sheet was foamed and increased in thickness compared to before vulcanization. Next, the sheet after primary vulcanization was left to stand in a room at 200°C for 4 hours to carry out secondary vulcanization.

[0041] Example 2 A non-foamed layer sheet was prepared as follows. 100 parts by mass of a silicone compound (product number: KE-561-U, for rubber hardness 60) manufactured by Shin-Etsu Chemical Co., Ltd. and 2.3 parts by mass of a vulcanizing agent (product number: C-3) manufactured by Shin-Etsu Chemical Co., Ltd. were mixed and kneaded to prepare a compound for sheet molding. Next, the compound after kneading was rolled through two rolls adjusted to a gap of 0.3 mm to be molded into a sheet. Such molding was performed once to prepare one sheet for the non-foamed layer. The other conditions were the same as those in Example 1.

[0042] Example 3 A sheet for a non-foamed layer was prepared as follows. 100 parts by mass of a silicone compound (product number: KE-981-U, for rubber hardness 80) manufactured by Shin-Etsu Chemical Co., Ltd. and 2.3 parts by mass of a vulcanizing agent (product number: C-3) manufactured by Shin-Etsu Chemical Co., Ltd. were mixed and kneaded to prepare a compound for sheet molding. Next, the compound after kneading was rolled through two rolls adjusted to a gap of 0.3 mm to be molded into a sheet. Such molding was performed once to prepare one sheet for a non-foamed layer. The other conditions were the same as those in Example 1.

[0043] Example 4 Two sheets for non-foaming layer were prepared under the same conditions as in Example 3. The foaming layer sheet was blended and molded under the same conditions as in Example 1. When the foaming layer sheet and the non-foaming layer sheet were laminated together, the foaming layer sheet was sandwiched between the two non-foaming layer sheets. Thereafter, lamination was performed in the same manner as in Example 1. The conditions for the primary vulcanization and secondary vulcanization performed after lamination were the same as in Example 1.

[0044] Comparative Example 1 100 parts by mass of silicone compound (product number: KE-541-U) manufactured by Shin-Etsu Chemical Co., Ltd., 2.3 parts by mass of vulcanizing agent (product number: C-3) manufactured by Shin-Etsu Chemical Co., Ltd., 1.0 part by mass of organic foaming agent "azobis-isobutyronitrile", and 1.0 part by mass of black pigment (product number: KE-COLOR-CB) manufactured by Shin-Etsu Chemical Co., Ltd. were mixed and kneaded to prepare a compound for sheet molding. Next, the compound after kneading was rolled through two rolls adjusted to a gap of 1.3 mm and molded into a sheet. As a result, a foam layer sheet similar to that of Example 1 was obtained. The conditions of the primary vulcanization and secondary vulcanization performed thereafter were the same as those of Example 1.

[0045] Comparative Example 2 A foam layer sheet was produced under the same conditions as in Comparative Example 1, except that the silicone compound (product number: KE-541-U) was changed to a silicone compound (product number: KE-561-U).

[0046] 2. Evaluation method Each sample in the Examples and Comparative Examples was subjected to the evaluation described in each of the following Test Examples in addition to the appearance observation. The evaluation of the compressive load and the tensile load were performed using an AG-20kN manufactured by Shimadzu Corporation.

[0047] (Test Example 1) Compressive load evaluation Each sample piece was cut into a circular shape with a diameter of 30 mm and compressed at a speed of 10 mm / min. The stress at each point was calculated from the load when the thickness of each sample piece was compressed by 10% and 50% and the dimensions of each sample piece. The calculated stress values ​​are shown as the compression load in Figure 7.

[0048] (Test Example 2) Tensile Load Evaluation Each sample piece was cut into a rectangular shape with a width of 20 mm and a length of 150 mm and clamped between chucks spaced 100 mm apart. Each clamped sample piece was pulled in the longitudinal direction at a speed of 500 mm / min. The stress at each point was calculated from the load when the chuck distance had elongated by 1%, 5%, and 10% after pulling, and the dimensions of each sample piece before pulling. The calculated stress values ​​are shown as tensile loads in Figure 7.

[0049] (Test Example 3) Sealing performance evaluation Each sample was cut into a doughnut shape with an outer diameter of 70 mm and an inner diameter of 50 mm and placed on a lower acrylic plate with a diameter of 70 mm. An upper acrylic plate with a diameter of 70 mm and a flange pipe attached to the top was placed on top of the sample. The inside of the flange pipe connected to the upper acrylic plate was filled with water to a height of 1 m and left to stand. After 30 minutes, the presence or absence of water leakage was evaluated. The evaluation results are shown in Figure 7.

[0050] (Test Example 4) Evaluation of resistance to bending The resistance to bending of each sample was evaluated by the amount of displacement at one end of the sample when the other end was fixed. The smaller the displacement, the less likely the sample is to bend. The evaluated deflection values ​​are shown in Figure 7 in the format of deflection (a, b, c) [mm]. In Figure 7, the horizontal deflection with the non-foamed layer on the bottom is shown as a, the horizontal deflection with the non-foamed layer on the top is shown as b, and the vertical deflection with the non-foamed layer facing left is shown as c.

[0051] 3. Evaluation results Fig. 7 shows the morphology and evaluation results of each sample of the examples and comparative examples. Note that the Z direction in Fig. 7 refers to the thickness direction in this specification, and the XY plane direction refers to the plane direction in this specification.

[0052] The results of the tensile load evaluation showed that Comparative Example 1 had a load of 0.003 N / mm at 1% elongation. 2 , Load 0.012N / mm at 5% elongation 2 , Load 0.024N / mm at 10% elongation 2 On the other hand, in Examples 1 to 4, the load at 1% elongation was 0.003 to 0.006 N / mm 2 , Load 0.014~0.038N / mm at 5% elongation 2 , Load at 10% elongation: 0.047~0.262N / mm 2 Thus, the tensile load of each Example was increased compared to Comparative Example 1, particularly when the elongation was 5% or more. Furthermore, even at an elongation of 1%, there was no decrease in the tensile load compared to Comparative Example 1. The large value of the tensile load indicates low flexibility in the planar direction (XY planar direction). Therefore, the flexibility in the planar direction of each Example was suppressed compared to Comparative Example 1 by providing a non-foamed layer.

[0053] As a result of the compression load evaluation, the load at 50% compression of Comparative Example 1 was 0.253 N / mm 2 , 10% compression load 0.043N / mm 2 On the other hand, in Examples 1 to 4, the load at 50% compression was 0.024 to 0.331 N / mm 2 , 10% compression load 0.003~0.045N / mm 2 As described above, the compression load of each Example did not change significantly from Comparative Example 1 in any case. The value of the compression load means the degree of flexibility in the thickness direction (Z direction). Therefore, the flexibility in the thickness direction of each Example was maintained without changing significantly from Comparative Example 1.

[0054] As a result of the sealing property evaluation, all of Examples 1 to 4 were leak-free, and each Example exhibited sealing properties comparable to those of Comparative Example 1. As a result of the deflection resistance evaluation, each Example exhibited a smaller deflection value, particularly in the horizontal direction, compared to Comparative Example 1. Also, no increase in deflection value was observed in the vertical direction. Therefore, the deflection resistance of each Example was comparable to that of Comparative Example 1, and was clearly improved in the horizontal direction.

[0055] From the above results, it can be said that each Example has less flexibility in the planar direction than Comparative Example 1, i.e., the conventional product, while other physical properties are maintained or even improved from the conventional product. [Industrial Applicability]

[0056] The sealing member according to the present invention can be used as a sealing member for a battery container. [Explanation of symbols]

[0057] 1...sealing member, 2...foam layer, 3...non-foam layer, 10...battery, 11...container, 12...upper lid, 13, 14...screw holes, 15...screw, 16...nut, 20...battery cell.

Claims

1. An annular seal member for sealing an opening and closing portion of an open-close type container for storing a plurality of battery cells, The sheet has at least one foamed layer and at least one non-foamed layer, A sealing member, characterized in that the foamed layer and the non-foamed layer are fixed in a laminated state in a thickness direction of the sealing member.

2. 2. The sealing member according to claim 1, wherein said foamed layer and said non-foamed layer are both layers of silicone rubber.

3. 2. The sealing member according to claim 1, wherein the non-foamed layer is laminated on both sides of the foamed layer.

4. 2. The sealing member according to claim 1, wherein the foamed layer is laminated on both sides of the non-foamed layer.

5. A method for manufacturing the seal member according to any one of claims 1 to 4, comprising the steps of: A blending step of blending the raw materials of the foamed layer and the non-foamed layer; a sheeting step of forming the foamed layer and the non-foamed layer into a sheet shape after the blending step; a lamination step of laminating the foamed layer sheet formed in the sheeting step and the non-foamed layer sheet; a vulcanization step of vulcanizing and hardening the sheets bonded in the bonding step; A method for manufacturing a sealing member, comprising:

6. A battery comprising the sealing member according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • JP1990000470U

  • Seal structure using gasket

    JP2012097896A

  • Electronic apparatus

    JP2018113105A

  • Foaming complex

    JP2018171916A

  • Multi-layer structure gasket and manufacturing method therefor

    JP2021014908A